Exploring Nurses’ Experience of Managing Attention and Mood in Post-Stroke Patients: A Qualitative Study - Tri Suraning Wulandari; Suhartini Ismail (Faculty of Nursing Universitas Padjadjaran, 2019)
Attention is an important aspect of cognitive development in the perspective of information processing, whereas mood is an affective aspect relating to expectations about positive or negative feelings. Decreased attention and mood in post-stroke patients can cause instability, cognitive impairment, and long-term rehabilitation. These impacts affect the patients’ activity daily living (ADL). Priority of post stroke patient care in hospital was priority on physical problem rather than psychological, social and spiritual problems. Nurses as caregivers in the hospitals should understand in manage bio-psycho-socio-cultural-spiritual problems in post-stroke patients. This descriptive study that used a descriptive qualitative research was conducted to describe the barrier of managing attention and mood in post stroke from the perspective of nurses. This research was a pilot study using qualitative design and involved six nurses at Temanggung General Hospital, Indonesia. The data collection was carried out using in-depth semi-structured interviews. The data analyzed using inductive content analysis. Five themes emerging from data included the nurse's focus on the physical problem, lack of awareness to manage attention and mood, unavailability of early assessment for attention and mood, family participation in nursing care and lack of information about the interventions in handling attention and mood. The initial assessment of attention and mood greatly encourages nurses to provide alternative or complementary nursing that can be administered in the hospital. Nurses’ understanding of knowledge and skills are essential to prevent the impact of reduced attention and mood. The management of attention and mood should be supported by all professional health providers, and facilities in hospitals, as well as the role of the family.